2020
DOI: 10.1038/s41598-020-62197-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a conductive biocomposite combining graphene and amniotic membrane for replacement of the neuronal network of tissue-engineered urinary bladder

Abstract: Biocomposite design. The sandwich-structured biocomposite material was constructed from frozen human Am and covered from the stromal side with two graphene layers. The stromal side was chosen due to its ultrastructure, which is irregular and offers a suitable scaffold for graphene attachment. Therefore the graphene layer could settle freely on pleated Am surface. Am preparation. Am was obtained according to the well-established protocol used in ophthalmology for Am transplantation Shortly, the donors was scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The high reinforcing properties of graphene are due to the two-dimensional structure with high specific surface area of 2630 m 2 g −1 26 . Graphene, having good biological properties, has been extensively studied in biological applications, including drug delivery 27 , biosensing 28 , tissue engineering 29 , and bioimaging 30 .…”
mentioning
confidence: 99%
“…The high reinforcing properties of graphene are due to the two-dimensional structure with high specific surface area of 2630 m 2 g −1 26 . Graphene, having good biological properties, has been extensively studied in biological applications, including drug delivery 27 , biosensing 28 , tissue engineering 29 , and bioimaging 30 .…”
mentioning
confidence: 99%
“…GO is a single-atom layered material composed of carbon, hydrogen and oxygen molecules through the oxidation of inexpensive and abundant graphite crystals [ 30 , 44 , 45 ]. Furthermore, GO has good biological properties and has been widely used in biomedical field, including drug delivery [ 46 ], cancer therapy [ 47 , 48 ], biosensing [ 49 ], tissue engineering [ 50 ], and bioimaging [ 51 ]. The use of GO can enhance cell proliferation and differentiation characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The constructs have been seeded with porcine UCs and SMCs derived from porcine detrusor. It has been demonstrated that the presence of graphene layer significantly increased electrical conductivity of the bio-composite and the contractile response indicated the effective SMCs stimulation [68].…”
Section: Mechanical Stimulation Of Scaffold Using a Bioreactormentioning
confidence: 99%